2015
DOI: 10.1177/0266242615569324
|View full text |Cite
|
Sign up to set email alerts
|

Financial statement filing lags: An empirical analysis among small firms

Abstract: This article examines financial statement filing lags among a sample of Belgian small firms. Our results indicate that around one-third of small firm financial statements are filed late (after the legal deadline), but that monetary sanctions could be an effective tool to encourage compliance with legal deadlines. Whereas the deadline and late filing sanctions are filing incentives, various factors, such as firm size and presence of an external financial statement audit, also affect financial statement filing l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
70
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(85 citation statements)
references
References 79 publications
10
70
1
4
Order By: Relevance
“…Secondly, small company accounts generally lack of a system of internal control, thus making independent confirmation of figures presented in the accounts problematic . Thirdly a time lag often occurs when small companies draw up their accounts [Luypaert et al, 2015], this delay further hinders the relevance of the information as a useful tool to determine the health of a firm . Ultimately, when it comes to business failure definitions many researchers are guided to the most appropriate failure definition based on the dataset available rather than vice versa, so a trade-off exists between ease of access to a dataset and an appropriate definition of business failure.…”
Section: Review Of Existing Definitions and Their Implicationsmentioning
confidence: 99%
“…Secondly, small company accounts generally lack of a system of internal control, thus making independent confirmation of figures presented in the accounts problematic . Thirdly a time lag often occurs when small companies draw up their accounts [Luypaert et al, 2015], this delay further hinders the relevance of the information as a useful tool to determine the health of a firm . Ultimately, when it comes to business failure definitions many researchers are guided to the most appropriate failure definition based on the dataset available rather than vice versa, so a trade-off exists between ease of access to a dataset and an appropriate definition of business failure.…”
Section: Review Of Existing Definitions and Their Implicationsmentioning
confidence: 99%
“…As public large-sized firms are under huge pressure to present financial statements to avoid reputational and market inefficiencies, the few studies about accounting information delays are mostly focused on SMEs. Luypaert et al [17] outlined why SMEs filed their financial statements late (more than seven months after the closing date of the accounting year) using a sample of Belgian private firms during 2006-2008. Specifically, Luypaert et al [17] showed that around 30% of Belgian SMEs filed late.…”
Section: General Considerationsmentioning
confidence: 99%
“…Luypaert et al [17] outlined why SMEs filed their financial statements late (more than seven months after the closing date of the accounting year) using a sample of Belgian private firms during 2006-2008. Specifically, Luypaert et al [17] showed that around 30% of Belgian SMEs filed late. Their conclusions are that external audit, size and age are determinants of late filing.…”
Section: General Considerationsmentioning
confidence: 99%
See 2 more Smart Citations